Performance Evaluation of Beacon Enabled IEEE 802.15.4 MAC for Mobile Wireless Sensor Networks under NS-2 - Muhammad, Javed; Kartinah, Zen; Halikul, Lenando; Hushairi, Zen (2013)
Wireless Sensor Network (WSN) has a large number of nodes capable of sensing, communicating and computing. WSNs have limitations due to limited storage, processing and transmission power. The IEEE802.15.4 Medium Access Control (MAC) protocol is used for low-rate wireless personal area network (LR-WPAN). LR-WPAN is basically designed for static wireless sensor networks. However, from literatures, we observed that IEEE802.15.4 is able to support weak mobility in mobile sensor networks [7]. This paper evaluates the IEEE802.15.4 MAC for strong mobility in mobile sensor network environments. We evaluate the performance of IEEE802.15.4 MAC based on both static and mobile coordinators, and taking into account two parameters which are speed and number of beacon orders. We observed the effect on association period, disassociation, and synchronization between the mobile node and the coordinator in strong mobility of mobile nodes. From the experiments, we obtained results on throughput, association and synchronization with different speed and beacon orders. We found that the IEEE802.15.4 cannot maintain association period in strong mobility. The weaknesses of mobile node association attempt and synchronization process degrade the overall performance of a network. We also identify some research problems that need to be addressed for successful implementation of MAC protocol with strong mobility in Mobile Wireless Sensor Networks.